Neural control of muscle lengthening: Task- and muscle-specificity - Hirofumi Sekiguchi; Kimitaka Nakazawa; Tibor Hortobágyi (Japanese Society of Physical Fitness and Sports Medicine, 2013)
We accomplish activities of daily living through a combination of or isolated isometric, shortening (concentric), lengthening (eccentric) contractions regarded as fundamental patterns of muscle activation. It has been widely recognized that a unique neural strategy may control lengthening contractions but it is still unclear if this neural strategy is uniform across muscles. Here we review evidence for task-specific differences in neural control of muscle lengthening and shortening as indexed by surface electromyographic activity, corticospinal excitability, anatomical properties, and motor unit behavior. The emerging hypothesis is that the neural control of task-specificity associated with muscle lengthening and shortening may not be uniform across all healthy human muscles.